INTEGRATION OF PSYCHOLOGICAL TECHNOLOGIES INTO PHYSICAL EDUCATION OF PRIMARY SCHOOLCHILDREN (International journal of artificial intelligence, 2025)
The article examines the possibilities of integrating psychological technologies into the system of physical education for primary schoolchildren.The purpose of the study is to substantiate and experimentally confirm the effectiveness of using psychotechnologies - including autogenic exercises, visualization, emotional self-regulation, and game-based methods - in the process of forming positive motivation for physical activity and strengthening the volitional sphere of students.The methods used included pedagogical observation, questionnaires, psychodiagnostics (assessment of anxiety and motivation levels), as well as a pedagogical experiment involving control and experimental groups. The obtained results demonstrated that the use of psychological technologies contributes to reducing academic anxiety, increasing interest in physical education classes, and developing stable self-control skills.It is concluded that the systematic inclusion of psychological and pedagogical tools in the content of physical education at the primary level is essential for achieving a holistic educational and developmental effect.